2018
DOI: 10.1038/s41388-018-0444-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species genomics identifies DLG2 as a tumor suppressor in osteosarcoma

Abstract: Leveraging the conserved cancer genomes across mammals has the potential to transform driver gene discovery in orphan cancers. Here, we combine cross-species genomics with validation across human-dog-mouse systems to uncover a new bone tumor suppressor gene. Comparative genomics of spontaneous human and dog osteosarcomas (OS) expose Disks Large Homolog 2 (DLG2) as a tumor suppressor candidate. DLG2 copy number loss occurs in 42% of human and 56% of canine OS. Functional validation through pertinent human and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 31 publications
5
69
0
Order By: Relevance
“…Synaptogenesis is a key process in neuronal differentiation, and mutations in genes involved in the formation of synapses have frequently been implicated in NDD (also termed shankopathies) 65 . Furthermore, DLG2 has been recently described as a tumor suppressor in osteosarcoma 46,47 . We propose that the dysregulation of Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptogenesis is a key process in neuronal differentiation, and mutations in genes involved in the formation of synapses have frequently been implicated in NDD (also termed shankopathies) 65 . Furthermore, DLG2 has been recently described as a tumor suppressor in osteosarcoma 46,47 . We propose that the dysregulation of Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The SHANK2 gene was found disrupted in 11 HR-NA tumors; 3 samples involved gene fusions that didn't appear in frame. DLG2, a newly described tumor suppressor in osteosarcoma 46,47 , was found disrupted in 10 samples based on SJ-BP and RD-BP analyses from a total of 14 samples, two of which involved gene fusion events. Both SHANK2 and DLG2 are located on chromosome 11q and play a role in the formation of postsynaptic density (PSD) 48 .…”
Section: Identification Of Genes Recurrently Altered By Svs In High-rmentioning
confidence: 99%
“…EGCG was proposed to affect cell proliferation and apoptosis through Hippo signaling pathway in oral cancer [43], but has not been studied in bladder cancer. While the role of DLG2 as a tumor suppressor gene in osteosarcoma [44] and miRNA target in ovarian cancer inhibiting cell migration [45] were reported, its involvement in bladder cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that DLG2 copy number loss occurs in 56% of canine osteosarcomas. Deleting the DLG2 gene in a murine model also accelerated the development of canine osteosarcoma [65].…”
Section: Osteosarcomamentioning
confidence: 97%
“…The study found SETD2 mutations in 21% of tumors across all three breeds of predisposed dogs (golden retrievers, Rottweilers and greyhounds). The gene DLG2, important in regulating cell division, migration and tumorigenesis, is also a viable tumor suppressor candidate of osteosarcoma [65]. One study found that DLG2 copy number loss occurs in 56% of canine osteosarcomas.…”
Section: Osteosarcomamentioning
confidence: 99%